LOCAL CULTURE-BASED ETHNOMATICS DEVELOPMENT IN MATHEMATICS DEVELOPMENT IN MATHEMATICS LEARNING TO IMPROVE CRITICAL THINKING SKILLS - siti sangadah; Zainur Wijayanto; Insanul Qisti Bariyyah; Ana Fitrotun Nisa (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
Integration of cultural elements into the learning process, especially in mathematics, functions as a strategic approach to create a contextual and interesting classroom environment. This study aims to develop ethnomatics-based mathematics learning media that integrates local culture to improve critical thinking skills of 5th grade elementary school students. This study is a type of research and development that refers to three stages: preliminary study, model development, and trial. The subjects of this study consisted of 66 fifth grade elementary school students in Klaten Regency, Central Java who were selected using purposive sampling techniques. The data collected quantitatively to determine the average score, by categorizing based on the evaluation table referred to by the criteria, then analyzed qualitatively. The preliminary study was conducted through observations related to local culture that is relevant to the concept of mathematics and a needs questionnaire. The product developed is a plasticine learning media in the form of traditional cakes as an aid in understanding the concept of geometry. The trial results showed significant improvements in four aspects of learning: conceptual understanding (from 70 to 90), critical thinking skills (from 74 to 89), collaboration (from 75 to 95), and local cultural knowledge (from 70 to 95). These findings indicate that ethnomatics based on local culture is not only effective in improving students' academic abilities, but also in strengthening cultural understanding and collaborative skills. Thus, this approach is worthy of being used as an innovative alternative in mathematics learning in elementary schools.